195k views
4 votes
Neeed help plz
2(x-3)+9=3(x+1)+x

2 Answers

7 votes

Answer: x = 0

Explanation:

Start by using the distributive property on the equation (when multiplying a number by an expression in parenthesis, multiply the number by every term in the parenthesis):

2(x - 3) + 9 = 3(x + 1) + x

2x - 6 + 9 = 3x + 3 + x

Simplify:

2x + 3 = 4x + 3

Subtract 2x from both sides:

3 = 2x + 3

Subtract 3 from both sides:

0 = 2x

Finally, divide both sides by 2:

0 = x

User Guy Schaller
by
5.9k points
3 votes

Answer:

x = 0

Explanation:

Step 1: Distribute

2x - 6 + 9 = 3x +3 + x

Step 2: Combine like terms

2x + 3 = 4x + 3

Step 3: Isolate x

3 = 2x + 3

0 = 2x

Step 4: Divide by 2

x = 0

And you have your final answer!

User Peteski
by
4.6k points